2022
DOI: 10.5194/hess-26-3901-2022
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nonlinearity and stability of streamflow recession characteristics under climate warming in a large glaciated basin of the Tibetan Plateau

Abstract: Abstract. The accelerated climate warming in the Tibetan Plateau after 1997 has profound consequences in hydrology, geography, and social wellbeing. In hydrology, the change in streamflow as a result of changes in dynamic water storage that originated from glacier melt and permafrost thawing in the warming climate directly affects the available water resources for societies of the most populated nations in the world. In this study, annual streamflow recession characteristics are analyzed using daily climate an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
2
0
0
Order By: Relevance
“…However, an explanation for this difference could be in the length of the dataset, with Sergeant using data from 1970-2000 and our study encompassed data from 1954-2020, an extra 40 years. Other studies agree with our findings of increased β values (e.g., McKenzie et al, 2021b;Ploum et al, 2019;Wang et al, 2022). (1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995) of βOC = 1.72.…”
Section: Temporal Change In Seasonality and Recession Behaviorsupporting
confidence: 93%
See 1 more Smart Citation
“…However, an explanation for this difference could be in the length of the dataset, with Sergeant using data from 1970-2000 and our study encompassed data from 1954-2020, an extra 40 years. Other studies agree with our findings of increased β values (e.g., McKenzie et al, 2021b;Ploum et al, 2019;Wang et al, 2022). (1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995) of βOC = 1.72.…”
Section: Temporal Change In Seasonality and Recession Behaviorsupporting
confidence: 93%
“…In the upstream catchments, the thawing active layer will allow for increasing subsurface flow, with spring having the shallowest thickness of the active layer and fall having the deepest thickness of the active layer, while in downstream catchments the thickness of the active layer can already be fluctuating within the areas of discontinuous permafrost, leading some areas to already have deep thickness of active layer as well as with streamflow of different seasons flowing from the upstream catchments creating a blend of spring, summer or fall discharge further obfuscating seasonal recessions. Increasing groundwater flow as found in studies from and Walvoord and Striegl (2007) lead researchers to suggest that this increase leads to more non-linearity in streamflow response and the increased storage capacity lengthens timescales and leads to the increased blending of streamflow seasonalities (Wang et al, 2022;Curran and Biles, 2021).…”
Section: Seasonal Shifts In Recession Behaviormentioning
confidence: 99%
“…It motivates many researchers to investigate the response of runoff to changes in climate and cryosphere (Han et al., 2019; Jiang et al., 2022; J. Wang et al., 2021). It is found that there are significant shifts in hydrological regimes including the runoff magnitude, streamflow recession, precipitation‐runoff relationship and water yield around 2000 (H. Li et al., 2022; X. Li et al., 2022; J. Wang et al., 2022), whereas the monotonic trend in runoff is not significant (as shown in our results).…”
Section: Discussionsupporting
confidence: 50%
“…It is found that there are significant shifts in hydrological regimes including the runoff magnitude, streamflow recession, precipitation-runoff relationship and water yield around 2000 (H. X. Li et al, 2022;J. Wang et al, 2022), whereas the monotonic trend in runoff is not significant (as shown in our results).…”
Section: Runoff Nonstationarysupporting
confidence: 40%